Effects of transformational and transactional leadership on job satisfaction - Yi, Zhang (2015)
Leadership style is important to employees’ job satisfaction. This study aims to examine the effect of leadership style on employees’ job satisfaction among service companies of Handan City in China. The questionnaires were firstly designed to collect data from the three service companies, namely hotel, travel agency and insurance companies. The 60 respondents who were employed in these service companies were selected as samples in this study. There were two independent variables which were transactional leadership and transformational leadership. Meanwhile, job satisfaction was selected as dependent variable. By using SPSS 19.0 version, the Reliability Test and Pearson Correlation test were firstly conducted to determine the relationship between independent variables and dependent variable. Then, the Multiple Regression analysis was conducted to determine the effect of leadership style, namely transactional leadership and transformational leadership, on job satisfaction respectively. The results revealed that both transactional leadership and transformational leadership were found to be positively related to job satisfaction of employees. In addition, the study also examined the intermediate effects of gender and age on job satisfaction. The results showed that the effects of gender and age were no significant on job satisfaction, implying they had no difference between gender an age on job satisfaction. The study has strategic implications that the managers should pay attention to leadership style to improve employees’s job satisfaction, which would contribure to the sustainable growth of service companies. In conclusion, the research could provide guideline to design policies on how to improve employees’ job satisfaction